HISTOLOGICAL STRUCTURE OF THE KINTAMANI DOG ON THE SEXUAL MATURITY PERIOD - Setiasih, Ni Luh Eka; Suastika, Putu; Heryani, Luh Gede Sri Surya; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2019)
The objective of this study was to determine the histological structure of uterus of the kintamani dogs on the sexual maturity period. In this study using five samples of uterine organs of the kintamani dog. The tissue were taken from corpus of the uterine. The histological structure was observed using hematoxylin-eosin (HE). Identification of the histological structure of uterus observed with a microscope at 100x and 400x magnification. The results showed the endometrial lining   consisted a single layer  of the columnar epithelium and lamina propria with tubular glands, myometrium consisted of smooth muscle and perimetrium with connective tissue, nerves and blood vessels